Propuesta para la adopción de la tecnología 5G en el cantón Bolívar - Moreira Santos, Edwin Wellington (2022)
The main objective of this degree work was to develop a proposal for the adoption of 5G technology to contribute to the improvement of advanced mobile service in Bolívar canton. The execution of this investigation was carried out in compliance with the specific objectives: to explore the advances of 5G technology, prepare a situational diagnosis, determine the feasibility and design an action plan. In the first objective, an exploration of the advancement of 5G technology and its impact in Latin America was carried out, with the help of the systematic review; in the second objective, a situational diagnosis was made with respect to the technological level in Bolívar canton using techniques such as descriptive statistics, in addition to mobile tools such as "OpenSignal" and "Network signal information"; in the third objective, it was possible to determine the feasibility of adopting this technology with its advantages, disadvantages, operational, technical, legal and economic feasibility, this with the "Cellular Antennas" tool and the Google Earth service; and in the fourth objective, an action plan was designed through the 5W2H methodological instrument, where mechanisms that contribute to the adoption of this advanced mobile service were proposed. Finally, it is concluded that 5G technology will undoubtedly reach the town, however, it requires a large investment to be able to meet the demand for the infrastructure and service quality in Bolívar canton.